Investigation on fatigue crack growth in MRT rail Part I - surface crack case - Ko, Ming Chan (2018)
Over the years, higher travelling speed and the ability to carry heavier loads have been achieved in the railway industry through technological advancements. However, it also resulted in higher traction forces and contact stresses, which may lead to faster wear rate, as well as accelerating Rolling contact fatigue (RCF) at the contact surface of both the rail and the wheel. The project seeks to understand crack initiation and propagation mechanism in rails due to RCF. In addition, the project also seeks to discuss how varying certain variables such as the material properties of the rail material may affect the rate of crack propagation, as well as the crack length propagation in the rail. With these understanding, it will allow us to maintain the rail more efficiently so as to prevent any catastrophic failures or fracture. To showcase the research, a two dimensional (2D) model will be build using the software program known as ABAQUS. The program allows for the simulation of crack growth and propagation within the rail as a result of continuous compressive cyclic cycles while changing certain variables simultaneously. The 2D model will be split into two phases, namely the cross section and front face of the rail. Through the simulations, the author seeks to deduce the relationship between the various variables with the rate of crack propagation, as well as crack length propagation. After the completion of the 2D simulation, the author will then create a 3D model in a bid to augment the deductions regarding the crack growth behaviour within the rail as a result of varying variables used in the simulation.